Draft Annual Plan 2003-2004 Government of Punjab - Planning Commission (Planning Commission, 2003)
As per 2001 census about 66 percent of the population of Punjab lives in its villages. About 39 percent workers of the total work force are engaged in Agriculture and allied sector. the contribution of this sector towards State's Gross State Domestic Product (GSDP) is 39.69 percent, which is higher than the national average of 27.50 percent. Therefore, Agriculture and allied sectors have to play a major role in the development of the State. The overall rate of growth in the State was 7 percent during 1999-2000, which was also higher than the national growth rate of 6 percent. 1.2 To generate employment in the state, especially in rural areas, there is a need for promoting industrialization and agro- processing industries.
Department of Planning Government of Punjab